SEMANTICS AND HERMENEUTICS - Luke, K. (Journal of Dharma, 1980)
The capacity to make use of language as a means of communication is a unique characteristic of the human species, and when a man makes some statement or other, his words convey a meaning to the bearer, or they may even call for interpretation, and " all interpretation is essentially linguistic." There are two distinct but closely related sciences dealing with the problems of meaning and interpretation, namely, semantics,2 and hermeneutics,8 and it is the purpose of this paper to try to bring out the significance of the former for the latter. Professional linguists have their own special techniques which cannot entirely be followed in this modest study because of typographical difficulties. Furthermore, their way of referring to scholarly publications is different from the one usually adopted in contributions that claim to he wissenschaftlich : we make use of the commonly accepted system of reference.